Mimicking ribonucleotide reductases: Biomimetic manganese complexes and their reaction with superoxide - MAGHERUSAN, ADRIANA MARIA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
An important discovery in class Ib ribonucleotide reductase’s chemistry has been the identification of a MnII2 active site, that required a superoxide anion (O2•–), rather than dioxygen (O2), to access a high-valent MnII2 oxidant. Many synthetic mononuclear Mn model complexes have been prepared to mimic the structures and reactivity of Mn-metalloenzymes. However, the reactivity of a MnII2 model complex with O2•– has never been investigated and this was the main objective of this thesis. The main topics of the work described in this thesis are the study of O2•– reactivity of MnII2 complexes, preparation and characterisation of intermediates, to mimic the active postulated intermediates observed in class Ib Mn2 RNRs. In chapter 2, we describe our initial discovery that complex [MnII2(O2CCH3)(N-Et-HPTB)](ClO4)2 (1) could be reacted with O2•– at low temperature (≤-40 °C), to form the metastable [MnIIMnIII(O2)(O2CCH3)(N-Et-HPTB)]+ (2). This species was characterised by electronic absorption spectroscopy, showing features at λmax = 460, 610 nm, typical of a Mn-peroxide species. EPR spectroscopy of 2 exhibited a 29-line signal characteristic of a MnIIMnIII entity. Furthermore, XANES suggested a formal oxidation state change of MnII2 in 1 to MnIIMnIII for 2. Moreover ESI-MS suggested a MnIIMnIII-peroxide complex. Upon activation with proton donors, the MnIIMnIII-peroxide (2) was capable of oxidising ferrocene and weak O-H bonds. These findings provided support for the postulated mechanism of O2•– activation at class Ib Mn2 RNRs.  In successive work, we were interested in mimicking the other Mn-intermediates observed in the catalytic cycle of class Ib RNRs. This involved the preparation of another MnIIMnIII-peroxide complex, investigation and characterisation of the species formed upon activation of the peroxide complex with proton donors. Therefore the reactivity of complex [MnII2(O2CCH3)2(BPMP)](ClO4) (4) with O2•– at low temperature (≤-80 °C) was explored, resulting in formation of a metastable species (5). Adduct 5 was characterised by electronic absorption and EPR spectroscopies, ESI-MS, displaying features of a MnIIMnIII-peroxide complex (5). Unlike adduct 2, whose MnIIMnIII-core proved to be unreactive at -40 °C, species 5 proved to be a nucleophilic oxidant in aldehyde deformylation. The preparation of a nucleophilic peroxo-MnIIMnIII oxidant (5) was reported in chapter 3. Next, the reactivity of the MnIIMnIII-peroxide (5) towards acids was investigated. This involved the screening of different reaction conditions as well as different sources of proton donors. Adduct 5 was susceptible to acids at low temperatures (≤-80 °C). The addition of strong acids (HClO4, HBF4) to 5 resulted in the formation of a metastable adduct (7). Adduct 7 exhibited electronic absorption features  typical of a mixed valent MnIIMnIII complex. Unfortunately, the EPR spectrum of 7 was saturated by a signal typical of a MnII species. Upon addition of strong acids to 5 the formation of a MnIIMnIII species (7) was postulated. The reactivity of 5 was also investigated towards weaker acids. Interestingly, the addition of pTsOH (1 or 2 equivalents) to 5 exhibited electronic absorption features and an EPR signal typical of a MnIIIMnIV species. Thus, by probing the reaction of peroxo adduct 5 with acids of different strength, distinct adducts formed. Upon addition of a strong acid to 5, a MnIIMnIII species was postulated while for reaction of 5 with low equivalents of a weak acid the formation of a mixed valent MnIIIMnIV species was proposed. The evidence obtained for formation of mixed valent MnIIMnIII and MnIIIMnIV species was important, as such species have been postulated as intermediates in the catalytic cycle of class Ib Mn2 RNRs.  The preparation of peroxo-MnIIMnIII species upon reaction of MnII2 complexes with O2•– was achieved in chapters 2 and 3. Besides, proof for formation of mixed valent MnIIMnIII and high valent MnIIIMnIV species was observed in chapter 4. Such adducts were postulated as intermediates in class Ib Mn2 RNRs. We tried to synthesise another MnII2 complex supported by the HPTP ligand. Firstly, when the reaction for the synthesis of the Mn2 complex supported by the HPTP ligand was performed in air, a mixed valent Mn6 complex was obtained. Nevertheless, the synthesis of a MnII2 complex bridged by HPTP, two perchlorate anions and two acetonitrile solvent molecules was achieved ([Mn2(ClO4-)2(CH3CN)2(HPTP)](ClO4-), 11) under anaerobic conditions. Further studies on the reactivity of this complex with O2•– will provide further insight into the catalytic cycle of class Ib Mn2 RNRs.  Besides the RNRs, we maintain a keen interest in the analogous catechol oxidase enzymes. These enzymes catalyse the oxidation of o-diphenols (catechols) to the corresponding quinones and contain a Cu2 core. In the last chapter (chapter 6) of this thesis, we explored synthetic CuII2 and MnII2 complexes as model systems for catechol enzymes. While CuII2 complexes have been widely investigated as catechol oxidase mimics, the catechol oxidase reactivity of MnII2 complexes has been less explored. A series of MnII2 and CuII2 complexes supported by the same poly-benzimidazole ligand framework were synthesised. The catecholase activity of these complexes in acetonitrile medium using 3,5-di-tert-butylcatechol (3,5-DTBC) as a substrate was investigated. The CuII2 complexes proved to be better catechol oxidase mimics (kcat values ~45 h-1) when compared to MnII2 complexes (kcat values ~8-40 h-1).
APPROVED
Keywords: Ribonucleotide reductase chemistry